What is the Status of Omani Parents on their Children's Healthy Lifestyle? - Hashem A. Kilani; Ibrahim A. Al-Qaryouti (Sultan Qaboos University, 2016)
The purpose of this study was to document the significance of the practices employed by parents that contribute to children's healthy lifestyle in Oman. Those practices encompassed the physical activity and inactivity, sedentary behaviour, nutritional knowledge, and its reflection on their children at early childhood class. Subjects consisted of 237 male and female parents of kindergarten children in the Sultanate of Oman. The researchers developed a twenty-three and a twenty-item questionnaire intended to measure the degree of parent involvement in their children's impact at acceptable levels of validity and reliability. (Amazingly, it was found that parents' healthy lifestyle were low in their habit practices (low in engagement to physical activity, sports and daily life activity) which showed a trend of sedentary lifestyle. Meanwhile, they did not encourage their children to participate in physical activity nor control them from staying away from being in front of TV screen and video games, too. In addition, their nutritional knowledge also scored low which affected their children's health negatively. It is, therefore, suggested that lifestyle concept should be inculcated in the learning process for children, and further analysis be made as to what extent the demographic category may influence parents' involvement towards their children's healthy lifestyle.